\(\sqrt{10-2\sqrt{21}}+\sqrt{10+2\sqrt{21}}\)
\(=\sqrt{7-2\sqrt{21}+3}+\sqrt{7+2\sqrt{21}+3}\)
\(=\sqrt{\left(\sqrt{7}\right)^2-2.\sqrt{7}.\sqrt{3}+\left(\sqrt{3}\right)^2}+\sqrt{\left(\sqrt{7}\right)^2+2.\sqrt{7}.\sqrt{3}+\left(\sqrt{3}\right)^2}\)
\(=\sqrt{\left(\sqrt{7}-\sqrt{3}\right)^2}+\sqrt{\left(\sqrt{7}+\sqrt{3}\right)^2}\)
\(=\left|\sqrt{7}-\sqrt{3}\right|+\left|\sqrt{7}+\sqrt{3}\right|\)
\(=\sqrt{7}-\sqrt{3}+\sqrt{7}+\sqrt{3}\)
\(=\sqrt{7}+\sqrt{7}=2\sqrt{7}\)
Ta có: \(\sqrt{10-2\sqrt{21}}+\sqrt{10+2\sqrt{21}}\)
\(=\sqrt{7}-\sqrt{3}+\sqrt{7}+\sqrt{3}\)
\(=2\sqrt{7}\)
đặt \(A=\sqrt{10-2\sqrt{21}}+\sqrt{10+2\sqrt{21}}\)
\(=>A^2=10-2\sqrt{21}+10+2\sqrt{21}+2\sqrt{\left(10-2\sqrt{21}\right)\left(10+2\sqrt{21}\right)}\)
\(=>A^2=20+2\sqrt{10^2-\left(2\sqrt{21}\right)^2}=20+2\sqrt{16}=20+2.4=28\)
\(=>A=\sqrt{28}=2\sqrt{7}\)